Rights And Obligations Of Stakeholders In The Local Financial Legal System - Yohanes D. Resi; Henrikus Renjaan (Eduvest - Journal of Universal Studies, 2024)
The financial relationship between the central and local governments is a mandate of the law. In the implementation of regional autonomy, regional financial management is fully given to local governments. So that local governments are stakeholders in the regional financial legal system. This study aims to determine the rights and obligations of stakeholders in the regional financial legal system. The method in this research is a literature review method with a qualitative approach. So that data is obtained through the results of various sources such as scientific books, research reports, scientific essays, theses and dissertations, regulations, decrees, yearbooks, encyclopedias, and other printed and electronic written sources. The results of the study found that the rights of stakeholders in the regional financial legal system are to plan and compile regional budgets, manage regional finances to meet community needs, and establish regional financial policies. While their obligations are to comply with laws and regulations related to regional financial management, submit financial reports in a transparent and accountable manner, and manage regional finances efficiently and effectively.